Evaluation of MUC1, MUC2, MUC5AC, and MUC6 Expression Differences in Lung Adenocarcinoma Subtypes by Using a Final Immunoreactivity Score (FIRS) - Melek BUYUK; Yasemin OZLUK; Dogu VURALLI BAKKALOGLU; Berker OZKAN; Pinar FIRAT; Dilek YILMAZBAYHAN (Federation of Turkish Pathology Societies, 2023)
Objective: Lung adenocarcinomas are divided into acinar, lepidic, papillary, micropapillary, and solid predominant subtypes according to the current World Health Organization (WHO) classification. We designed this retrospective study to demonstrate profiles of MUC expression (MUC1, MUC2, MUC5AC, and MUC6) of different histologic patterns within the same tumor among pulmonary adenocarcinomas and investigate correlations of MUC expression with clinicopathologic features. Material and Method: We analyzed the expression of mucins (MUC1, MUC2, MUC5AC, and MUC6) in a series of 99 resected lung adenocarcinomas, which included a total of 193 patterns (71 acinar, 30 lepidic, 25 papillary, 20 micropapillary, 34 solid and 13 mucinous) and calculated a final immune reactivity score (FIRS) per tumor. Results: MUC1 IRS scores were significantly higher in lepidic and solid patterns compared with mucinous patterns (p=0.013). MUC2 expression was seen only in three cases (1 acinar, 2 mucinous). MUC5AC and MUC2 expression was more common in mucinous patterns (p<0.001 and p=0.028, respectively). MUC6 expression was only detected in seven patterns and the expression was weak. No significant difference was seen among histologic patterns for the staining scores of MUC6. Mucinous adenocarcinoma differed from other histologic subtypes regarding MUC1 and MUC5AC expression. Mucinous adenocarcinoma showed less MUC1 expression with lower IRS scores and higher MUC5AC expression. Tumor size (p=0.006), lymphatic invasion (p=0.018), vascular invasion (p=0.025), perineural invasion (p=0.019), MUC1 IRS scores (p=0.018), and MUC1 IRS scores >8.5 (p=0.018) were significant predictors for lymph node metastasis. Conclusion: An alternative scoring for MUC1 can be used as a predictor for lymph node metastasis regardless of the histologic subtype.